2021
DOI: 10.1155/2021/4404185
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Non-Pharmacological Interventions for Irritable Bowel Syndrome: A Systematic Review

Abstract: Introduction. Given the complexity of the therapeutic management of irritable bowel syndrome (IBS), alternative non-pharmacological therapies are frequently offered to patients. The aim of this study was to conduct a systematic review in order to establish the current evidence base for non-pharmacological interventions (body-directed and mind-body therapies) in the management of IBS. Materials and Methods. The literature was searched in several electronic databases (PubMed (including Medline), Web of Science (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…On one hand, a Cochrane systematic review including17 RCTs reported that the effective rate of acupuncture for IBS was better than pharmacological interventions (Manheimer et al, 2012a), but the pharmacological interventions were sundry and included Chinese herbal formula, probiotics, pinaverium bromide, and sulfasalazine, etc. Another systematic review similarly confirmed that at 6-month follow-up, acupuncture was more beneficial for overall symptoms of IBS compared to standard medical Frontiers in Physiology frontiersin.org treatment (Amsallem et al, 2021). The recent research was validated again and reported that acupuncture may be a more effective treatment than PEG 4000/pinaverium bromide in terms of improving the symptoms of IBS (Pei et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…On one hand, a Cochrane systematic review including17 RCTs reported that the effective rate of acupuncture for IBS was better than pharmacological interventions (Manheimer et al, 2012a), but the pharmacological interventions were sundry and included Chinese herbal formula, probiotics, pinaverium bromide, and sulfasalazine, etc. Another systematic review similarly confirmed that at 6-month follow-up, acupuncture was more beneficial for overall symptoms of IBS compared to standard medical Frontiers in Physiology frontiersin.org treatment (Amsallem et al, 2021). The recent research was validated again and reported that acupuncture may be a more effective treatment than PEG 4000/pinaverium bromide in terms of improving the symptoms of IBS (Pei et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…To date, there is a systematic review from 2014 assessing the effectiveness of OMT for IBS symptoms with promising results [20]; however, it was judged as low in the AMSTAR-2 quality assessment tool by a recent overview of systematic reviews [21]. There are another two systematic reviews from 2021, however, the focus was not only on OMT, as they included other types of interventions, such as physiotherapy, and acupuncture [22,23]. Hence, it was necessary to update the evidence regarding OMT and IBS, and nevertheless a meta-analysis was still missing, therefore this systematic review and meta-analysis aims to summarize the current evidence about the effectiveness of OMT in patients with IBS for the IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%